Formulation Development and Evaluation of Herbal Hair Oil - Mahawar, Vandana; Yaduwanshi, Phool Singh; Jain, Gaurav; Lokesh, Kavita R (Journal of Neonatal Surgery, 2025)
Context: Plants with antioxidants and antibacterial properties are helpful in increasing blood circulation and thus good for hair growth and for the treatment of other hair related problems. Aim: The objective of the present research work is to develop an herbal hair oil formulation by using extract of Aloe barbadensis, Murray koenigii, Bacopa monnieri, Annona squamosal, Nardostachys jatamansi, Trigonella foenum-graecum and Nigella sativa having more potency for curing hair fall. Method: Hair oil is prepared by mixing all plant ingredients with the base oil and heated for some time to prepare herbal oil and then its evaluation is done by using parameters like physical properties, pH and viscosity, acid value, saponification value, primary irritation. Antioxidant activity was determined using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) method by taking ascorbic acid as standard and antimicrobial properties is determined by cup plate method by taking fluconazole (for fungi) and Ciprofloxacin (for bacteria) as standard. Results: Herbal hair oil A4 and A5 formulation shows good antioxidant and antimicrobial activity thus good for hair growth. Both formulations are good from stability and other general parameter point of view